Determining The E-Learning Implementation Gap According to The Standards of The European Association of Distance Teaching Universities: A Case Study in A Number of Public and Private Colleges in Baghdad - Tamara T. Kamal, Dr.Areej S. Khalil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to determine the e-learning implementation gap following the standards of the European Association of Distance Teaching Universities, which are strategic management, curriculum design, academic program design, academic program delivery, staff support and student support by identifying the gap and diagnosing the strengths and weaknesses of the colleges investigated. The problem of the study was the emergence of many problems and challenges facing e-learning in higher education institutions. Therefore, the need to adopt international and approved standards to work on appeared, where elearning has become an essential part of the educational process and inherent in traditional education even after the demise of the Corona pandemic. The case study method was adopted to achieve the objectives of the study and to reach the The required scientific facts, as well as the use of the checklist as a tool for collecting data and information. The study cases were a number of public and private colleges investigated in Baghdad, namely (College of Administration and Economics - Baghdad University, College of Administration and Economics - Al-Mustansiriya University, Al-Esraa University College and College of Administration and Economics - Uruk National University). The results showed that the College of Administration and Economics, University of Baghdad ranked first in terms of the percentage of implementation, followed by the College of Administration and Economics, Al-Mustansiriya University, and then the Al-Esraa University College, which amounted to (69%, 64%, 61%) respectively, but this showed the opposite in the College of Administration and Economics, University of Uruk, with a large gap in implementation that amounted to (81%). The study concluded with a number of recommendations ز The most prominent of which was the interest in spreading the culture of e-learning in higher education institutions through conferences or workshops that are held face to face or electronically for the purpose of conferencing and to increase awareness and interest in it as it has become an integral part of the educational process and cannot be dispensed with at present and in the future.